Clinical Course and Electron Microscopic Findings in Lymphocytes of Patients with DRAM2-Associated Retinopathy - Kuniyoshi, Kazuki (Int J Mol Sci, 2020)
DRAM2-associated retinopathy is a rare inherited retinal dystrophy, and its outcome has not been determined. A single retinal involvement by a mutation of the DRAM2 gene is unexplained. We found three unrelated patients with a disease-causing DRAM2 variant in a biallelic state from 1555 Japanese individuals of 1314 families with inherited retinal dystrophy. We reviewed their medical records and examined their peripheral lymphocytes by transmission electron microscopy (TEM). Patient 1 was a 38-year-old woman who complained of night blindness and reduced vision. She developed macular degeneration at age 43 years. Patients 2 and 3 were a man and a woman both of whom noticed night blindness in their 30s. Both had a degeneration in the macula and midperiphery in their 40s, which progressed to a diffuse retinal degeneration in their 60s when their vision was reduced to hand motions. Three novel DRAM2 variants were identified. TEM of the lymphocytes of Patients 1 and 2 showed abnormal structures in 40.6% and 0.3% of the peripheral lymphocytes, respectively. We concluded that the DRAM2-associated retinopathy of our patients was a progressive rod-cone dystrophy, and the visual outcome was poor. The systemic effect of DRAM2 mutations may be compensable and have variations.